Supervisi Pendidikan Era Society 5.0 - Inom Nasution; Aji Pramudya; Amaluddin Tanjung; Dina Oktapia; Khoirun Nisa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
Low education human resources in Indonesia, especially educators or teachers who are less professional in carrying out their work, can be the cause of low levels of education in this country. One way to improve the quality of education is through the professionalization of teachers or through educational supervision. Supervision through various methods, education corrects educational problems helping, supervising, guiding, and directing educators towards professionalism in its goal is to improve education and address problems with it. Educational supervision supports teachers in developing lesson plans that will produce the desired learning outcomes. Supervision is an integral part of efforts to improve learning achievement and teacher quality. Supervision or supervision is an effort to provide services to education, especially teachers. Education supervision is also a process of controlling and evaluating activities to ensure that all educational activities are carried out according to plan, as well as activities to improve and correct if there are deviations that will interfere with the process of achieving goals. Reviewing educational supervision in order to improve teacher professionalism is the purpose of this. This article is written using the literature study method in the form of a number of literature tasks related to the management of research materials, reading and recording, and information collection techniques. Some are obtained on the basis of research studies.